Isolation and pharmacological characterization of a short neurotoxin, α-elapitoxin-Bf1b (α-EPTX-Bf1b) from Malaysian Bungarus fasciatus - Ahmad Rusmili, Muhamad Rusdi; Mustafa, Mohd Rais; Othman, Iekhsan; Hodgson, Wayne C. (2013)
Introduction: In Malaysia and other countries in South East Asia, kraits (genus Bungarus) are considered to be a medically important species. The Golden banded krait (Bungarus fasciatus) is one species found in Malaysia. Like many other krait species, Bungarus fasciatus venom has previously been reported to contain a number of postsynaptic neurotoxins that cause blockade of neuronal transmission involving the nicotinic acetylcholine receptor. However, not many of these toxins have been isolated and fully characterized. Here, we would describe the isolation and pharmacological characterization of a novel short neurotoxin that we named α- elapidtoxin-Bf1b. Methods and Results: The toxin was purified by a combination of gel filtration, cation-exchange and reverse-phase chromatography. Based on mass spectrometry and sequencing data, the toxin showed high homology with another toxin, Neurotoxin 3FTx-RI that has previously only been detected in the Bungarus fasciatus venom gland transcriptome. The toxin has an approximate molecular mass of 6.9 kDa and caused concentration-dependent and time-dependent neuromuscular blockade when tested in the indirectly-stimulated chick biventer cervicis muscle preparation. The toxin is also partially reversible after continuous washing. Monovalent Bungarus fasciatus and neurotoxic polyvalent antivenoms were found to be ineffective in reversing the neurotoxicity effect in indirectly-stimulated chick biventer cervicis preparation. Conclusion: We have isolated a novel short neurotoxin from Malaysian Bungarus fasciatus. This toxin is perhaps the first short neurotoxin from Bungarus fasciatus that has been reported to be resistant to both monovalent Bungarus fasciatus and neurotoxic polyvalent antivenoms.